2016
DOI: 10.1002/mar.20914
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Negatively Valenced Emotional Expressions in Online Reviews on the Reviewer, the Review, and the Product

Abstract: The authors examine the effects of negatively valenced emotional expressions (NVEE; e.g., intense language, all caps, exclamation points, emoticons) in online reviews and reveal important boundary conditions for their effects. Specifically, Study 1 showed that NVEE directly promote review helpfulness and damage attitude toward the product when used by experts. In contrast, for novices, their use of NVEE was considered a poor reflection on them and failed to directly affect attitude toward the product. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 53 publications
1
49
3
Order By: Relevance
“…It was found that when a reviewer expresses negative emotions they are perceived irrational but when positive emotions are expressed the reviewer is perceived as rational. Another study conducted by Folse et al (2016) received similar results with negative emotions.…”
Section: Emotions Embedded In Online Reviewssupporting
confidence: 60%
See 4 more Smart Citations
“…It was found that when a reviewer expresses negative emotions they are perceived irrational but when positive emotions are expressed the reviewer is perceived as rational. Another study conducted by Folse et al (2016) received similar results with negative emotions.…”
Section: Emotions Embedded In Online Reviewssupporting
confidence: 60%
“…Based on the previous discussion, developed hypotheses and previous studies (Folse et al, 2016;Kim & Gupta, 2012;Srivastava et al, 2008;Welsh 2003), it is suggested that emotions influence review helpfulness through price fairness first and then reviewer rationality. As a result, the following hypothesis is proposed:…”
Section: Perceived Rationality Of the Reviewermentioning
confidence: 99%
See 3 more Smart Citations